Antecedentes históricos do currículo da AMOP - Noffke, Ana Paula (2017)
This work presents a historical background of the Basic Curriculum for the Municipal Public School of AMOP and the origin of this Association. To understand what were the influences to produce this material and trying to find a solution the following problem: how and why an association of Municipalities, as a representative of the state, capitalist social development, published a curriculum with a dialectical conception of education? We started with information from the document itself, which was created under the coordination of AMOP Pedagogical Department (2003), created after the extinction of ASSOESTE (2002), an entity created by the MEC / OAS Special Multinational Project in 1980. Our hypothesis was that the influence in the creation of education present in the Curriculum has its origin, largely, in the work accomplished by ASSOESTE. Therefore, the research sought historical antecedents of this referential, in order to know the structure of the West Region and the events that implied in the transformation of the area, analyzing the impacts caused in education; To know the origin of AMOP, analyzing the historical and political context of its creation and its role in regional development; To know the MEC / OAS Special Multinational Project, and analyzing the historical and political context in which it was drawn up and executed, as well as some of its contributions to the education of the Western Region; To know the history of ASSOESTE, the context of their foundation and some of their contributions to the education of the West, its process of extinction and consequent creation of the Pedagogical Department of AMOP. To the completion of this dissertation, readings of historical texts, bibliographies, minutes, statutes, and laws were made, and this dissertation was constituted by exploratory and investigative research, based on the assumptions that reality is dynamic, in constant development, and that men make history, and do it according to the physical conditions at their disposal. The results obtained with this work indicate that the creation of AMOP occurred for strategic military government reasons, and it played a fundamental role in consolidation of the conservative modernization of agriculture that caused great changes in the region, as well as the construction of Itaipu. To promoting search for solutions to the problems caused by these two phenomena, the Special Project MEC / OAS was created and implemented, which had great contributions to education, which one of them being the creation of ASSOESTE. The research on ASSOESTE allowed us to prove our hypothesis that was the work carried out by ASSOESTE that influenced the beginning of the education of the AMOP’s curriculum. It also allowed us to understand that its extinction was not only due to financial issues, but also to the political ideology assumed by its Pedagogical Department.